A randomised trial to assess the efficacy and safety of chlorproguanil/dapsone + artesunate for the treatment of uncomplicated Plasmodium falciparum malaria. - Fanello, C; Karema, C; Ngamije, D; Uwimana, A; Ndahindwa, V; Van Overmeir, C; Van Doren, W; Curtis, J; D'Alessandro, U (2008)
We tested the efficacy and safety of chlorproguanil/dapsone co-administered with artesunate (CD+A) for the treatment of uncomplicated Plasmodium falciparum malaria in children compared with amodiaquine+sulfadoxine/pyrimethamine (AQ+SP) at two different sites in Rwanda. The trial was open label and 800 patients were randomly assigned to AQ+SP (n=400) or CD+A (n=400). Patients were hospitalised for 3 days and then followed-up weekly until Day 28 after treatment. Clinical and parasitological outcomes were recorded. Results showed that neither treatment was adequately efficacious. At one site, the adequate clinical and parasitological response (ACPR), PCR-adjusted, was 73.3% in the CD+A arm and 87.8% in the AQ+SP arm (P<0.001), and at the second site the ACPR, PCR-adjusted, was 70.5% in the CD+A arm and 38.1% in the AQ+SP arm (P<0.001). The combination CD+A is considered an alternative to, or replacement for, SP in Africa because CD has been shown to be effective in patients for whom SP treatment has failed and, with its short half-life, it is expected to exert less selection pressure for resistant parasites than SP. However, the results of this trial indicate that in an area of high SP resistance, CD+A may not be the best choice.